Strategi Pemasaran Untuk Menarik Minat Masyarakat Pada Menu Tradisional Semanggi - Surabaya - Citra Anggraini Tresyanto (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2016)
Modern menu capable of easily sliding the existence of traditional menus first existing in the community. It also makes the young generation does not recognize traditional menus available. One example is the typical menu is a menu Semanggi Surabaya. People are starting trouble finding the menu, and existence without innovation has blurred its presence in the community, especially the younger generation. It is unfortunate if this clover menu should disappear from the heritage of traditional culinary riches. But there must also be the right strategy for the menu clover to stay alive in the community. Lovelock and Wright (2002: 13-15) developed the marketing mix (marketing mix) into integrated service management by using an approach 8P (elements Product, Place, cyberspace, and time, and education Promotion, Price and other user outlays, Process, Productivity and quality, People, Physical evidence). The 8P approach is certainly able to assess and establish new strategies appropriate for the development of clover menu. With modernization and government intervention products that facilitate the sellers, the presence of clover menu will continue to exist in society.